1998
DOI: 10.1046/j.1365-2133.1998.02218.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermal oedema assessed by high frequency ultrasound in venous leg ulcers

Abstract: Oedema is considered a key pathogenic factor in the development of venous leg ulcers. The purpose of this study was to determine the localization of oedema in legs with ulcers. Twelve patients with 13 venous leg ulcers (one bilateral), with a duration of 7-18 months, were examined by high-frequency B-mode ultrasound scanner. This was performed at three sites in the leg (low, middle and upper sites of the lower leg). In the same group of patients, the legs without ulcers were used as controls. The echogenicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 29 publications
5
27
0
1
Order By: Relevance
“…One study evaluated lymphatic drainage in a series of patients with unilateral leg ulcers, comparing it with the contralateral healthy leg and noting a decrease in lymphatic function in the leg with venous ulcers [48]. Another study constituting an essential component in the pathogenesis of this condition reported that chronic venous ulcers usually present a significant increase in edema focused on the papillary dermis, and further corroborated these results [49]. These findings have led some authors to conclude that impaired lymphatic drainage may be as important as venous pathology in chronic venous ulcers [27,48].…”
Section: Survival Probabilitysupporting
confidence: 50%
“…One study evaluated lymphatic drainage in a series of patients with unilateral leg ulcers, comparing it with the contralateral healthy leg and noting a decrease in lymphatic function in the leg with venous ulcers [48]. Another study constituting an essential component in the pathogenesis of this condition reported that chronic venous ulcers usually present a significant increase in edema focused on the papillary dermis, and further corroborated these results [49]. These findings have led some authors to conclude that impaired lymphatic drainage may be as important as venous pathology in chronic venous ulcers [27,48].…”
Section: Survival Probabilitysupporting
confidence: 50%
“…In the evening, the increased hydrostatic pressure in the veins of the lower legs, which develops with upright position, is transmitted to the microcirculation. Late at night, hydrostatic pressure is known to play a lesser role and pressures are redistributed 23 ; this has been demonstrated in studies using high-frequency ultrasound 24 and has been reinforced by results of magnetic resonance imaging of the skin. 25 Venous hypertension causes disturbed microcirculation and pathologic changes of the capillaries, with repeated tissue congestion and decongestion, extravasation of red blood cells, and release of proinflammatory cytokines due to activation of monocytes, 26 macrophages, 27 or neutrophils, 28 such as interleukin 1b (IL-1b), IL-6, tumor necrosis factor a, 29 vascular endothelial growth factor, 30 expression of intercellular adhesion molecules, 31 transforming growth factor b1, 32 and mast cell infiltration.…”
Section: Discussionmentioning
confidence: 88%
“…Ultrasound imaging has enabled the understanding of the water content of the upper dermis by demonstrating the features of the water reservoir at this level. 13 Ultrasound use shows diurnal and regional variation in water content of the epidermis and the dermis, and this is affected by age and influenced by postural factors, 14 external mechanical factors, 15 or even by the transfusion of a liter of saline. 16 The control of the permeability of the vascular bed supplying the epidermis is dependant on Starling's Law (1905), but the way in which the epidermis can also modify the permeability of the blood vessels as a result of production of mediators of inflammation that include prostaglandin or cytokines has become increasingly well understood.…”
Section: Epidermis and Its Blood Supplymentioning
confidence: 99%